PENGARUH RISIKO INVESTASI TERHADAP RETURN SAHAM DENGAN UKURAN BANK SEBAGAI VARIABEL MODERATING (Studi Pada Bank Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013 – 2017) - Hastin Wijayani; Sri Hermuningsih (SEGMEN Jurnal Manajemen dan Bisnis, 2020)
The aim of this study is to find out (1) The Effect of Investment Risk on Stock Returns in Bank Size as a Moderating Variable (Study on list of banks at Indonesia Stock Exchange in the year of 2013 - 2017) (2) Variable influence on credit risk, market risk, liquidity risk, capital risk towards stock returns. (3) The effect of moderated bank size towards variable of credit risk, market risk, liquidity risk, capital risk towards stock returns on the list of banks at Indonesia Stock Exchange in 2013 - 2017. The sample of this research uses 43 list of companies at Indonesia Stock Exchange. The method of collecting the data was taken from www.idx.com by taking the annual report starting from 2013 until 2017, while the data were analyze using multiple regression analysis and Moderated Regression Analysis (MRA), and the classical assumption test that consists of multicollinearity test, test normality, heteroskedasticity test, and autocorrelation test. The result of this study shows that (1) Credit Risk has a significant and positive impact on stock returns, (2) Market Risk a significant and positive impact on stock returns, (3) Liquidity Risk has a significant and positive impact on stock returns, (4) Capital Risk has a significant and positive impact on stock returns, (5) Bank size can moderate the relationship between credit risk and stock returns, (6) Bank size can moderate the relationship between market risk and stock returns, (7) Bank size can moderate the relationship between liquidity risk and return shares, (8) Bank size can moderate the relationship between capital risk, and stock returns. Keywords: Credit Risk, Market Risk, Liquidity Risk, Capital Risk, Bank Size, Stock Return